Rec. a Dante Alighieri (2010. Trad., intr., notas Jorge Vaz de Carvalho). Vida nova. Lisboa: Relógio d’Água - Marnoto, Rita (2011)
(2011). Rec. [a Dante Alighieri (2010. Trad., intr., notas Jorge Vaz de Carvalho). Vida nova. Lisboa: Relógio d’Água]. Colóquio Letras, 178, 215-218. ISSN 0010 1451